Fenestrated Pavement To Catch-Up Talent: Hackathons & Bootcamps - et. al., Esther Zionia.A , (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In this exterminator era, every organization crawls to be topper in their industry. To be on the top, every organization should have a successful employee who works for the company. Talented employees should be captured. One of the best ways to identify top talents is by conducting Hackathons and boot camps. From the Hackathons and boot camps, an employer can easily identify the top talented employees who can work for their organization. This research paper is an attempt to analyze the relationship between Hackathons and talent acquisition, the impact of Hackathons in talent acquisition and the major reason for hiring talented employees through Hackathons and boot camps with particular reference to Chennai. IT/ITES Sector employers are the respondents. The descriptive survey research design was used in this research. The hypothesis was tested using different statistical tools such as Multiple Regression, Correlations, and Weighted mean average. Using a simple random sampling technique, 245 respondents were chosen. From the analysis, it was revealed that virtual Hackathons, Interactive Hackathons, Industry Hackathons, and Internal recruiting Hackathons have a strong impact on talent acquisition. Hackathons and boot camps have a strong relationship with talent acquisition. The organization uses Hackathons and boot camps to identify the top talents, it reduces the time and cost of hire, an employer can easily identify the innovative thinkers and one of the best way to beat HR and employee referral filter. From this research, it has been identified that most of the organizations do adopt the Hackathons and boot camps strategy to hire talented employees.